The Role of Debt to Ratio and Profitability in Economic Growth and Company Development - Susanthi, Putu Rani; Kremer, Hendri; Hazriyanto, Hazriyanto; Ciptoputro, Vincentius Ade Arianto; Sari, Asih Purwana (Prodi Akuntansi FEBM Universitas Maritim Raja Ali Haji, 2024)
This study analyses the relationship and influence of Debt Asset Ratio (DAR) on company profitability. The data used in this study were obtained from the financial reports of companies listed on the Indonesia Stock Exchange during 2018-2022. The analytical method used is simple linear regression using statistical software. The steps are planning, collecting, analyzing, and interpreting data to answer research questions. DAR and profitability as variables in this study, population, and samples from 6 companies for five years. The influence of Debt to Asset Ratio applied to Company Profitability was analyzed using the linear regression statistical method. Debt to Asset Ratio is the independent variable, and Company Profitability is the dependent variable. The results of the correlation analysis found a linear relationship between the variables. The results of the regression analysis found that there was a shallow level of influence. This study has several limitations on the number of samples, variables, and industrial sectors studied. In addition, other factors also need to be considered-some recommendations for further research. They expanded the study sector, examining other factors such as accounts receivable turnover and company size.